The Effect of Anti-Stigma Campaign to Depressive Disorders on Instagram towards Students’ Anxiety Attitude - Winata, Cecilia Liusca; Pratamawaty, Benazir Bona (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
Digital activism has rapidly developed thanks to technological advancements, including campaigns that utilize media to address the stigma surrounding mental illness. These anti-stigma campaigns aim to reduce stigma and raise awareness about mental health. According to the WHO, depression is a common mental disorder that is associated with high rates of suicide. This study aimed to determine the effect of an anti-stigma campaign for depressive disorders on Instagram on students' anxiety attitudes using quantitative method. The presence or absence of feelings of anxiety, nervousness, anxiety, and fear of physical danger when around people with depressive disorders was used to assess anxiety attitudes. The researcher collected data by distributing questionnaires online via Google Form to respondents who met the criteria they set. The population used in this study consisted of active students aged above 18 years residing in Java Island, and the sample size for this research was 383 individuals determined using convenience sampling technique. The data from respondents was analyzed using the IBM Statistical Package for Social Sciences (SPSS) version 26 software and a simple linear regression analysis. According to the research findings, the anti-stigma campaign for depressive disorders had no significant influence on students' anxiety attitudes.